IMPROVING THE "HARDSKILLS" AND "SOFTSKILLS" OF TEACHERS IN VOCATIONAL EDUCATION ORGANIZATIONS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
In article is given the concepts of "soft" and "hard" skills and their importance in the development of a professional in a professional field, and notes the general and specific features of the approaches to understanding "softskills" and "hardskills" competencies in research in this area.